2020
DOI: 10.1136/emermed-2019-209069
|View full text |Cite
|
Sign up to set email alerts
|

Are referrals to hospital from out-of-hours primary care associated with National Early Warning Scores?

Abstract: BackgroundThe National Early Warning Scores (NEWS) is used in various healthcare settings to augment clinical decision making, and there is growing interest in its application in primary care. This research aimed to determine the distribution of NEWS among patients in UK out-of-hours (OOH) general practice and explore the relationship between NEWS and referral of patients to hospital.MethodsA historical cohort study using routinely collected data from the Birmingham Out-of-hours general practice Research Datab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 10 publications
(10 reference statements)
0
13
0
Order By: Relevance
“…This is similar to the observed time between symptom onset and COVID-19 death in other settings. 13, 14 Evidence for the role of NEWS in acute illness in community settings is growing, 15 16 17 18 19 but to date, only one descriptive study has provided empirical data on NEWS in care homes. 6 A recent systematic review on the use of NEWS in assessing unwell COVID-19 patients in primary care suggested that enthusiasm for its use may be premature.…”
Section: Discussionmentioning
confidence: 99%
“…This is similar to the observed time between symptom onset and COVID-19 death in other settings. 13, 14 Evidence for the role of NEWS in acute illness in community settings is growing, 15 16 17 18 19 but to date, only one descriptive study has provided empirical data on NEWS in care homes. 6 A recent systematic review on the use of NEWS in assessing unwell COVID-19 patients in primary care suggested that enthusiasm for its use may be premature.…”
Section: Discussionmentioning
confidence: 99%
“…Referrals to secondary care were identi ed from the recorded consultation outcome using methods previously described. (11)…”
Section: Discussionmentioning
confidence: 99%
“…A recent study of an out-of-hours primary care service calculated NEWS retrospectively from physiological variables obtained at the time of assessment. 17 The individual physiological observations were known to the clinician, but not summarised as an aggregate score. NEWS was a poor predictor of whether an individual patient was subsequently referred acutely to secondary care.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%